Shortfalls and Solutions for Meeting National and Global Conservation Area Targets. Issue 5 (24th February 2015) - Butchart, Stuart H.M.; Clarke, Martin; Smith, Robert J.; Sykes, Rachel E.; Scharlemann, Jörn P.W.; Harfoot, Mike; Buchanan, Graeme M.; Angulo, Ariadne; Balmford, Andrew; Bertzky, Bastian; Brooks, Thomas M.; Carpenter, Kent E.; et al.
Abstract: Governments have committed to conserving ≥17% of terrestrial and ≥10% of marine environments globally, especially "areas of particular importance for biodiversity" through "ecologically representative" Protected Area (PA) systems or other "area‐based conservation measures", while individual countries have committed to conserve 3–50% of their land area. We estimate that PAs currently cover 14.6% of terrestrial and 2.8% of marine extent, but 59–68% of ecoregions, 77–78% of important sites for biodiversity, and 57% of 25, 380 species have inadequate coverage. The existing 19.7 million km 2 terrestrial PA network needs only 3.3 million km 2 to be added to achieve 17% terrestrial coverage. However, it would require nearly doubling to achieve, cost‐efficiently, coverage targets for all countries, ecoregions, important sites, and species. Poorer countries have the largest relative shortfalls. Such extensive and rapid expansion of formal PAs is unlikely to be achievable. Greater focus is therefore needed on alternative approaches, including community‐ and privately managed sites and other effective area‐based conservation measures.